An agronomic assessment of greenhouse gas emissions from major cereal crops - VAN GROENIGEN, CORNELIS JAN (My University, 2012)
Agricultural greenhouse gas (GHG) emissions contribute approximately 12% to total global anthropogenic GHG emissions. Cereals (rice, wheat, and maize) are the largest source of human calories, and it is estimated that world cereal production must increase by 1.3% annually to 2025 to meet growing demand. Sustainable intensification of cereal production systems will require maintaining high yields while reducing environmental costs. We conducted a meta-analysis (57 published studies consisting of 62 study sites and 328 observations) to test the hypothesis that the global warming potential (GWP) of CH4 and N2O emissions from rice, wheat, and maize, when expressed per ton of grain (yield-scaled GWP), is similar, and that the lowest value for each cereal is achieved at near optimal yields. Results show that the GWP of CH4 and N2O emissions from rice (3757 kg CO2 eq ha-1 season-1) was higher than wheat (662 kg CO2 eq ha-1 season-1) and maize (1399 kg CO2 eq ha-1 season-1). The yield-scaled GWP of rice was about four times higher (657 kg CO2 eq Mg-1) than wheat (166 kg CO2 eq Mg-1) and maize (185 kg CO2 eq Mg-1). Across cereals, the lowest yield-scaled GWP values were achieved at 92% of maximal yield and were about twice as high for rice (279 kg CO2 eq Mg-1) than wheat (102 kg CO2 eq Mg-1) or maize (140 kg CO2 eq Mg-1), suggesting greater mitigation opportunities for rice systems. In rice, wheat and maize, 0.68%, 1.21%, and 1.06% of N applied was emitted as N2O, respectively. In rice systems, there was no correlation between CH4 emissions and N rate. In addition, when evaluating issues related to food security and environmental sustainability, other factors including cultural significance, the provisioning of ecosystem services, and human health and well-being must also be considered.
PUBLISHED
Keywords: Environmental Science; Climate change